2004
DOI: 10.1002/nau.20084
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of urinary and general symptoms and correlation with other clinical parameters in interstitial cystitis patients

Abstract: IC patients had significantly higher scores for the seven urinary symptoms compared to controls. The duration of disease was found to be correlated with the group of seven urinary symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Another scoring is the University of Wisconsin Symptom Instrument (U-W). The U-W scoring has been validated again recently [12]. The study showed that IC patients had significantly higher scores for the seven urinary symptoms compared to controls.…”
Section: Symptom Scoresmentioning
confidence: 99%
“…Another scoring is the University of Wisconsin Symptom Instrument (U-W). The U-W scoring has been validated again recently [12]. The study showed that IC patients had significantly higher scores for the seven urinary symptoms compared to controls.…”
Section: Symptom Scoresmentioning
confidence: 99%